MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MUATAN BAHASA INDONESIA KELAS V MENGGUNAKAN MODEL KREASI DI SEKOLAH DASAR - Tri Ambangsih; Fathul Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' critical thinking skills in learning Indonesian which are still low due to the lack of group discussions, one-way methods, and assignments that are not yet HOTS-based. The solution applied is the KREASI model, a combination of Problem Based Learning, Think Pair Share, and Mind Mapping. Through Classroom Action Research in elemntay school, the results showed that critical thinking skills, and learning outcomes had increased significantly. The KREASI learning model has proven to be effective in creating active, collaborative and meaningful learning that can improve learning outcomes.